2018
DOI: 10.1016/j.compchemeng.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Population balance model and experimental validation for reactive dissolution of particle agglomerates

Abstract: PDF/A is an ISO-standardized version of the Portable Document Format (PDF) specialized for the digital preservation of electronic documents. The extension in the file name is pdf. PDF/A differs from "normal" PDF in that features ill-suited for long-term archiving are omitted. PDF/A embeds all fonts used in the document within the PDF file, so that the user of your file will not have to have the same fonts that you used to create the file installed on their computer in order to read it. Recommended versions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A theoretically based control application was completed by Rohani’s research group, and they successfully obtained metastable crystals with a narrow size distribution. Zhao et al suggested a population balance model that considered the physical constraints to simulate the inseparable shrinkage and breakage of the agglomerated particles during the reactive dissolution by the continuous stirring. The coupled equations were solved by the high-order moment-conserving method of classes.…”
Section: Process Control Of Crystalline Pharmaceutical Productsmentioning
confidence: 99%
“…A theoretically based control application was completed by Rohani’s research group, and they successfully obtained metastable crystals with a narrow size distribution. Zhao et al suggested a population balance model that considered the physical constraints to simulate the inseparable shrinkage and breakage of the agglomerated particles during the reactive dissolution by the continuous stirring. The coupled equations were solved by the high-order moment-conserving method of classes.…”
Section: Process Control Of Crystalline Pharmaceutical Productsmentioning
confidence: 99%
“…In this work, we propose a method for MC in which the system's evolution in time is not followed by numerical integration of a system of ODEs, but by integrating the time dependent discretized PBE analytically and advancing in time in relatively long discrete intervals. Via a number of practical examples, it will be shown that the present method can be applied to a broad range of problems: five practical tests cases taken from the literature are considered, i.e., the emulsification (Becker et al, 2014), ageing cellulose process (Ahmad et al, 2015), cooling crystallization (Choong and Smith, 2004), reactive dissolution (Zhao et al, 2018), and liquid-liquid extraction . Although these examples are totally distinct from each other, the source terms in PBE have fundamentally different nature: in the four first cases aggregation of particles can be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…the Gear's method (ode15s stiff solver of Matlab). The batch cooling crystallization (Choong and Smith, 2004) and reactive dissolution (Zhao et al, 2018) presented in table 1, containing the time dependent growth and nucleation processes, are selected as practical cases to assess the performance of the ATS.…”
Section: Introductionmentioning
confidence: 99%